Respon Fisiologis Pulutan (Urena lobata L.) terhadap Polusi Udara di Lingkungan Industri - Winda, Winda; Kardhinata, Harso; Nurtjahja, Kiki; Fauziah, Ida (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Air pollution, primarily originating from transportation and industrial activities, has become a major concern in the context of environmental health. This study aims to investigate the relationship between air pollution and the morphological characteristics of leaves as well as the stomatal density of the pulutan plant (Urena lobata L.) in polluted environments within the industrial area of Medan and unpolluted environments in Percut Sei Tuan, Medan, North Sumatra. The research method employed is ex-post facto with a laboratory approach to the polluted industrial area. Experimental results indicate that the stomatal density on pulutan leaves in the polluted area, specifically in the Industrial Zone of Medan, is 17.27/mm2, whereas in the unpolluted area, namely Percut Sei Tuan, it is 896.81/mm2. This difference provides insights into the negative impacts of air pollution on pulutan plants, highlighting the importance of maintaining air quality for ecosystem health and human well-being.